The Effect of Local Taxes, Local Retribution, and Capital Expenditures on Local Own-Source Revenue: (Evidence from Bengkulu Regency) - Ul Albab, Farah Nisa; Ramadhani, Rizki; Komariyah, Erna Fitri (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2020)
This study examines the impact of local tax, local retribution, and capital expenditure on the local own-source revenue of the Bengkulu Regency from 2013 to 2017. This study utilizes the actual data of the actual local government budget from the Indonesian Audit Board. 50 data from 10 cities were sampled representing Bengkulu Regency. This study uses multiple regressions to examine the effect. The result shows that local tax and capital expenditure have a positive significant effect on Local Own-Source Revenue, while local retribution does not affect.